Noninvasive cardiac-specific biomarkers for the diagnosis and prevention of vascular stenosis in cardiovascular disorder - Pulukool, Sujith Kumar; Srimadh Bhagavatham, Sai Krishna; Vijay, Sudarshan K.; Almansour, Abdulrahman I.; Chaudhary, Sandeep; Abuyousef, Farah; Saleh, Na’il; Tripathi, Pratima (Frontiers in Pharmacology, 2024)
Non-invasive biomarkers could play a significant role in timely diagnosis, detection and management for vascular stenosis events associated with cardiovascular disorders. The study aimed to investigate high sensitivity troponin I (hs-TnI), cardiac troponin I (c-TnI) and high sensitivity C-reactive protein (hs-CRP) that may be used solely or in combination in detecting the extent of vascular stenosis in CVD patients. Methodology: 274 patients visiting with dyspnea/orthopnea complaints visiting the to cardiologists were enrolled in this study. Angiographic study was conducted on the enrolled patients to examine of stenosis in the five prominent vessels (LDA, LCX, PDA/PLV, RCA and OM) connected to the myocardium. Samples from cases suspected to be having coronary artery stenosis were collected, and subjected to biochemical evaluation of certain cardiac inflammatory biomarkers (c-TnI, hsTn-I and hs-CRP) and to check their sensitivity with the level of vascular stenosis. The extent of mild and culprit stenosis was detected during angiographic examination and the same was reported in the form significant (≥50% stenosis in the vessels) and non-significant (<50% stenosis in the vessels) Carotid Stenosis... We observed that 85% of the total population enrolled in this study was suffering from hypertension followed by 62.40% detected with sporadic episodes of chest pain. We found that most of the subjects (42% of the total population) had stenosis in their LAD followed by 38% who had stenosis in their RCA. Almost 23% patients were reported to have stenosis in their LCX followed by OM (18% patients), PDA/PLV (13%) and only 10% patients had blockage problem in their diagonal. 24% of the subjects were found to have stenosis in a single vessel and hence were categorized in the Single Vessel Disease (SVD) group while 76% were having stenosis in two or more than two arteries (Multiple Vessel Disease). hs-TnI level was found to be correlated with the levels of stenosis and was higher in the MVD group as compared to the SVD group. Conclusion: hs-TnI could be used as a novel marker as it shows prominence in detecting the level of stenosis quite earlier as compared to c-TnI in the CVD patients admitted for angiography.